1988
DOI: 10.1007/bf01907109
|View full text |Cite
|
Sign up to set email alerts
|

Early changes in collateral blood flow to ischemic myocardium and their influence on bimodal vulnerability during the first 30 min of acute coronary artery occlusion in dogs

Abstract: Coronary collateral blood flow and its changes during the first 30 min of acute coronary artery occlusion were studied in 34 anesthetized dogs to clarify its influence on the vulnerability of the heart in this first arrhythmic phase. Collateral flow was determined with 9-micron tracer microspheres (TM) injected at 1, 10 and 30 min after acute proximal occlusion of the left circumflex (LCX, n = 30) or left anterior descending (LAD, n = 4) coronary artery. The post-mortem selective retrograde coronary angiograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

1989
1989
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 32 publications
0
4
0
1
Order By: Relevance
“…However, in the present study, swine anaesthetized with medetomidineketamine-fentanyl showed a substantially higher incidence of ischaemia-induced ventricular brillation than swine anaesthetized with pentobarbital. This nding cannot be ascribed to differences in known determinants of ischaemia-induced ventricular brillation such as pre-ischaemic heart rate (Wainwright & Parratt 1993), body temperature (Mouritzen & Andersen 1966, Mortensen et al 1993, size of ischaemic area (Verdouw & Hartog 1986), collateral blood ow (Yoshida & Downey 1986, von Mutius et al 1988, and arterial pH (Dong et al 1967). A positive correlation between pre-ischaemic heart rate and occurrence of VF during ischaemia has been shown in swine (Wainwright & Parratt 1993).…”
Section: Discussionmentioning
confidence: 99%
“…However, in the present study, swine anaesthetized with medetomidineketamine-fentanyl showed a substantially higher incidence of ischaemia-induced ventricular brillation than swine anaesthetized with pentobarbital. This nding cannot be ascribed to differences in known determinants of ischaemia-induced ventricular brillation such as pre-ischaemic heart rate (Wainwright & Parratt 1993), body temperature (Mouritzen & Andersen 1966, Mortensen et al 1993, size of ischaemic area (Verdouw & Hartog 1986), collateral blood ow (Yoshida & Downey 1986, von Mutius et al 1988, and arterial pH (Dong et al 1967). A positive correlation between pre-ischaemic heart rate and occurrence of VF during ischaemia has been shown in swine (Wainwright & Parratt 1993).…”
Section: Discussionmentioning
confidence: 99%
“…VEGF R1 (Flt-1) plasma soluble form binds to VEGF plasma and is of particular importance as a functional regulator of angiogenesis. VEGF regulates inflammatory responses, angiogenesis, and vasculogenesis through VEGF R1 and VEGF R2 mediators (8).…”
Section: Vegf Kinase Receptorsmentioning
confidence: 99%
“…; von Mutius et al . ). This is in agreement with observations in patients with long‐standing coronary artery disease, where only in approximately one‐quarter to one‐third of the cases was collateral function sufficient to prevent ischaemia during brief coronary occlusion (Wustmann et al .…”
Section: Introductionmentioning
confidence: 97%